Vitamin D levels of obesity and non-obesity health workers: a cross-sectional study in Dr. Sardjito General Hospital/Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada, Yogyakarta - Siti Nur Rohmah; Dwita Dyah Adyarini; Prenali Dwisthi Sattwika; Anastasia Evi Handayaningsih; Hemi Sinorita; Vina Yanti Susanti (Universitas Gadjah Mada, 2022)
Obesity is one of the causes of chronic diseases, such as diabetes, hypertension, stroke, cancer, dyslipidemia, and heart disease. It is considered a financial burden on national health insurance since it drains the largest health fund. The study aimed to determine the difference in vitamin D levels in obese and non-obese health workers and analyze the factors that influence it. This was a cross-sectional study of the obese and non-obese health workers at Dr. Sardjito General Hospital, Yogyakarta. A total of 50 subjects, including 25 obese and 25 non-obese subjects were involved. Serum vitamin D levels was determined by ELISA. There was no significant difference between the obese and non-obese groups on vitamin D status (p<0.365). Vitamin D deficiency was found in 10% of subjects, whereas insufficient vitamin D levels were found in 46 and 44% of subjects, respectively. Vitamin D deficiency was more common in the obese (12%) than non-obese (8%) group. Contrarily, vitamin D insufficiency was more common in the non-obese (56%) than obese (36%) group. The serum vitamin D levels in the obese [30.08 (14.67-101.71) ng/mL] was not significantly different compare to those non-obese [28.54 (14.38-54.41) ng/mL] (p = 0.691). The multivariate analysis significantly showed that outdoor activities <30 min had a 7.061 times greater risk of having vitamin D deficiency/insufficiency compared to outdoor activities >30 min (OR 7.061; 95% CI: 1.064-46.872; p=0.043). In conclusion, there is no significant difference in vitamin D levels between the obese and non-obese groups. Vitamin D deficiency/insufficiency is more common in non-obese subjects than in obese subjects. Outdoor activity <30 min is a risk factor for vitamin D insufficiency/deficiency despite living in a tropical country with abundant sunlight throughout the year.